Clinical application of middle descending colon-double lumen ostomy with distal stoma narrowing in the treatment of anorectal malformation - Guoxian Huang; Wenni Li; Lili Ma; Xin Lei; Xiangde Lin; Yuandong Chen; Bo Xu (BMC, 2024)
Abstract Background Anorectal malformations (ARMs) are the most common congenital anomaly of the digestive tract. And colostomy should be performed as the first-stage procedure in neonates diagnosed with intermediate- or high-type ARMs. However, the most classic Pe˜na's colostomy still has some disadvantages such as complicated operation procedure, susceptibility to infection, a greater possibility of postoperative incision dehiscence, difficulty of nursing and large surgical trauma and incision scarring when closing the stoma. We aimed to explore the effectiveness of middle descending colon-double lumen ostomy (MDCDLO) in the treatment of high and intermediate types of anorectal malformations. Methods We retrospectively reviewed the data of patients who underwent MDCDLO for high or intermediate types of ARMs between June 2016 and December 2021 in our hospital. The basic characteristics were recorded. All patients were followed up monthly to determine if any complication happen. Results There were 17 boys and 6 girls diagnosed with high or intermediate types of ARMs in our hospital between June 2016 and December 2021. All 23 patients were cured without complications such as abdominal incision infection, stoma stenosis, incisional hernia, and urinary tract infection in the postoperative follow-up time of 6 months to 6 years except one case of proximal intestinal prolapse was restored under anesthesia. Conclusion MDCDLO offers the advantages of simplicity, efficiency, safety, mild trauma, and small scarring in the treatment of high and intermediate types of anorectal malformations.